Hydrated C60 fullerene enhances parthanatos and induces autophagy-related biomarkers in glioblastoma cell line - Faraj, Aryan; Viktor,; Tykhomyrov, Artem; Baydas, Giyasettin; Aslan, Abdullah; Agca, Can Alı (My University, 2022)
Glioblastoma is one the most aggressive type of brain cancers, which is resistant to resistant chemo- and radio-therapy. Nanoparticles of C60 fullerene derivates develop anticancer activity in various models. In contrast to many chemotherapy agents, this fullerene absolutely nontoxic in wide range of concentrations with respect to normal cells. C60 fullerene is a promising candidate for many biomedical applications. Therefore, we investigated the effect of water soluble hydrated C60 fullerene (HyC60Fn) on the expression of PARP, Beclin1, LC3, and GFAP in human glioblastoma U373 cell. Cell viability and migration were detected by MTT and wound healing-scratch assay, respectively. The expression of PARP, Beclin1, and LC3 were analyzed by western blotting and GFAP was detected with immunocytochemistry. HyC60Fn in a range of doses 0.5 – 2.0 µM decreased cell viability in a dose-dependent manner. Furthermore, the doses of HyC60Fn 1.0 and 2.0 µM noticeably suppressed glioblastoma cell migration. Mechanistically, we defined that HyC60Fn markedly up-regulated Beclin-1 and ratio of LC3-II/LC3-I expression as autophagy markers. Furthermore, water soluble HyC60Fn activated cleaved PARP fragment and consequently parthanatos in glioblastoma U373 cells. Present results demonstrate that HyC60Fn could initiate anti-tumor effect via the combination of severe autophagy flux and parthanatos in glioblastoma cells. Thus, HyC60Fn affects the cell death machinery, at least partially, through modulating glioblastoma cells reactivity and programmed cell death. Our findings suggest that pristine hydrated C60 fullerene could be a promising anti-cancer therapeutics and further study is required.
Keywords: Glioblastoma; Autophagy; C60 hydrated fullerene; Parthanatos